ESENSI PROSEDUR DISMISSAL DALAM TAHAP PRA-PERSIDANGAN SENGKETA TATA USAHA NEGARA - Aufa Wira Prakasa; Zakki Adlhiyanti (Fakultas Hukum Universitas Borneo Tarakan, 2022)
AbstractDismissal procedure is part of the pre-trial which decides the admissibility of the lawsuit. The administrative court chief holds the authority to examine the substance of the lawsuits in which previously has formally reviewed by the clerk. This article reviews the dismissal procedure regulations and the essence of this procedure in the administrative pre-trial. Using normative methodology, this research reveals that the dismissal procedure is regulated in the Law No 5 year 1986 jo Law No 9 year 2004 jo Law No 51 year 2009 on Administrative Court. In addition, the Supreme Court also issues the Supreme Court Regulation No 2 year 1991 on The Guidance of The Administrative Court Law Implementation. Furthermore, this research also comes to understanding that the dismissal procedure plays important role in the trial which are: 1) maintains the law and justice; 2) provides legal certainty; 3) creates harmonize relation between community and apparatus; 4) supports the check and balance principle for officials.Keywords: dismissal procedure; lawsuit; dispute; essence.AbstrakProsedur dismissal merupakan bagian dari rangkaian proses penentuan kelolosan gugatan dalam tahap pra-persidangan. Kewenangan atas prosedur ini dipegang oleh Ketua Pengadilan sebagai penilai substansi materiil suatu gugatan yang terlebih dahulu ditinjau secara formil oleh Panitera Pengadilan. Permasalahan yang akan dikaji dalam artikel ini mencakup ketentuan apa saja yang mengatur tentang prosedur dismissal dan esensi atau hakikat dari prosedur ini dalam tahap pra-persidangan. Artikel ini menggunakan metode yang berlandaskan penelitian hukum normatif. Dengan menggunakan pendekatan perundang-undangan, penulis menemukan bahwa UU 5/1986 tentang PTUN jo UU No 9/2004 jo UU No 51/2009 telah menyediakan seperangkat ketentuan mengenai prosedur dismissal yang didukung oleh SEMA 2/1991 tentang Petunjuk Pelaksanaan Beberapa Ketentuan dalam UU 5/1986 tentang PTUN. Esensi dari prosedur dismissal ini ialah: 1) Menegakkan hukum dan keadilan secara universal; 2) Menyediakan kepastian hukum bagi subjek dan objek sengketa TUN; 3) Menciptakan hubungan yang harmonis antara masyarakat dan aparatur TUN; dan 4) Menjunjung tinggi prinsip check and balance bagi para pejabat administrasi negara.Kata Kunci: Prosedur Dismissal, Gugatan, Sengketa, Esensi